2010
DOI: 10.1007/s00464-010-1148-1
|View full text |Cite
|
Sign up to set email alerts
|

Damage to the spermatic cord by the Lichtenstein and TAPP procedures in a pig model

Abstract: Both the technique and the mesh material have an impact on integrity of spermatic cord and testicular function. According to the results of this study, the laparoscopic TAPP procedure using a large-pore PVDF mesh has the least effect compared to preoperative values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 24 publications
1
13
0
1
Order By: Relevance
“… 59 Animal studies have shown considerable structural changes in the cord and testicle after hernia repair, more pronounced after the use of mesh. 59 , 61 , 62 In clinical studies, mesh repairs have negative effects on testicular perfusion and testicular volume, and reduce testosterone levels and sperm motility during the early postoperative period. 59 , 63 However, long-term follow-up has not shown statistically significant differences in testicular perfusion or spermatogenesis compared to preoperative values.…”
Section: Complications: Prevention and Treatmentmentioning
confidence: 99%
“… 59 Animal studies have shown considerable structural changes in the cord and testicle after hernia repair, more pronounced after the use of mesh. 59 , 61 , 62 In clinical studies, mesh repairs have negative effects on testicular perfusion and testicular volume, and reduce testosterone levels and sperm motility during the early postoperative period. 59 , 63 However, long-term follow-up has not shown statistically significant differences in testicular perfusion or spermatogenesis compared to preoperative values.…”
Section: Complications: Prevention and Treatmentmentioning
confidence: 99%
“…Postoperative agenesis is a critical issue. Especially in boys and men, both the surgical technique and the mesh material have an impact on the integrity of the SC and on testicular function[ 82 - 84 ]. Contact with mesh material may cause sterility in male patients[ 85 ].…”
Section: Agenesismentioning
confidence: 99%
“…To address these problems, the use of models of small laboratory animals seems to be ideal owing to the size similarity of their VD with that of neonates, infants, and toddlers. Some of studies seeking for the ideal techniques of vasovasostomy have been performed on rats, rabbits, and pigs and have suggested efficient and easy-to-perform surgical techniques for VD injury repair 14,[18][19][20][21][22][23][24][25] . However, none of them has considered VD injury repair from a complex clinical point of view that encompasses the fea-sibility of surgery with the use of only the operating loupe, and the difference between contusion of the VD and the results of vasovasostomy techniques in terms of patency and inflammation rates.…”
Section: Introductionmentioning
confidence: 99%